0149 Modelling of occupational exposure to hexavalent chromium. (23rd June 2014) - Pesch, Beate; Kendzia, Benjamin; Hauptmann, Kristin; Van Gelder, Rainer; Hahn, Jens-Uwe; Zschiesche, Wolfgang; Behrens, Thomas; Brüning, Thomas
Abstract : Objectives: To assess level and trend of exposure to hexavalent chromium (Cr(VI)) in chromium-exposed occupations for the estimation of lung cancer risks in community-based studies. Method: This analysis was based on 3666 personal measurements and auxiliary data compiled in the German MEGA database from 1988–2009. Cr(VI) was determined spectrophotometrically at 540 nm after reaction with diphenylcarbazide. We assigned jobs tasks with known Cr(VI) exposure using coded and textual information about the workplaces. Measurements below the limit of quantification (LOQ) were multiply imputed according to their distribution above LOQ. Statistical modelling was performed to the log-transformed Cr(VI) concentrations to adjust for duration and reason of sampling. Results: Cr(VI) exposure could be assessed for eight out of 30 jobs tasks with known Cr(VI) exposure. The majority of measurements (53%) were collected in welders (N = 1930), which we further detailed by welding technique. Spray painting and the welding of stainless steel with shielded metal welding were associated with adjusted geometric means above 5 µg/m 3, the permissible exposure level of the U.S. Occupational Safety and Health Administration. We could not detect an overall time trend in the Cr(VI) concentrations. Conclusions: Exposure to Cr(VI) varied by occupation and job task, particularly between welding techniques, but less across calendar time. Supplemental occupational questionnaires should be administered in community-based studies when estimating the lung cancer risk of Cr(VI).